The Influence of Work Culture and Leadership Style on Employee Performance at Yanks & Brits English Institute - Baene, Efianus; Nora Anisa Br. Sinulingga (SEAN Institute, 2021)
This study aims to determine the effect of work culture and leadership style on employee performance of Yanks & Brits. The research model uses a quantitative research model. The sample in this study were all employees of Yank & Brits Medan with a total of 21 employees. Data analysis using multiple linear regression test. The results showed that work culture (X1) has a significant value of 0.004 <0.05, which means that there is an influence between work culture on employee performance at the Yanks & Brits English Institute, and the results of the T test for the leadership style variable (X2) that the significant value is 0.000 <0.05. which means that there is an influence between work culture on employee performance at Yanks & Brits English Institute. Based on the results of the F test, it is known that the Sig value is 0.000 <0.05, so work culture and leadership style simultaneously have a significant effect on employee performance at the Yanks & Brits English Institute. Based on the results of the analysis and discussion that has been presented, it can be concluded that all independent variables, namely work culture and leadership style simultaneously affect the employee performance variable by 51.0% while the remaining 49.0% is influenced by other variables not included in the model.